Experimente in der Wirtschaftsinfromatik zu Kreativität - Ein systematischer Literaturüberblick und Implikationen für Geschäftsmodellmodellierungstools - Relard, Sebastian

Visualisierung von Taxonomien: Ein systematischer Überblick - Kemadjou, Rostand Ndoumi

Taxonomie zu Taxonomie-Nutzungsgründen - Wolfförster, Lukas

Entwicklung und Vergleich von Messkriterien anhand statistischer Methoden zur Optimierung der Leistungserbringung im IT-Unternehmen Diebold Nixdorf im Global Service Delivery Management - Patzer, Christfof

Beziehungen innerhalb und zwischen Geschäftsmodellen: Systematische Analyse durch Geschäftsmodell-Modellierungssprachen - Dowbysch, Michael

A Case for a New IT Ecosystem: On-The-Fly Computing - Karl, Holger; Kundisch, Dennis; Meyer auf der Heide, Friedhelm; Wehrheim, Heike (Business & Information Systems Engineering)

A Framework for Measurable Value Propositions of Mobile Applications - N., N.

Model-Based Product Configuration in Augmented Reality Applications - N., N.

Design and Implementation of a Crowd-based Prototype Validation Platform - N., N.

Jumping, dumping, and pumping: Three mental principles for idea generation to activate software-based tools in business model innovation - Szopinski, Daniel (Proceedings of the 32nd Bled eConference)

Because your taxonomy is worth it: Towards a framework for taxonomy evaluation - Szopinski, Daniel; Schoormann, T.; Kundisch, Dennis (Proceedings of the 27th European Conference on Information Systems (ECIS))

Business Models of Store-Oriented Software Ecosystems: A Variability Modeling Approach - Gottschalk, Sebastian; Rittmeier, Florian; Engels, Gregor (Business Modeling and Software Design)
In the last years, store-oriented software ecosystems are gaining more and more attention from a business perspective. In these ecosystems, third-party developers upload extensions to a store which can be downloaded by end users. While the functional scope of such ecosystems is relatively similar, the underlying business models differ greatly in and between their different product domains (e.g. Mobile Phone, Smart TV). This variability, in turn, makes it challenging for store providers to find a business model that fits their own needs. To handle this variability, we introduce the Business Variability Model (BVM) for modeling business model decisions. The basis of these decisions is the analysis of 60 store-oriented software ecosystems in eight different product domains. We map their business model decisions to the Business Model Canvas, condense them to a variability model and discuss particular variants and their dependencies. Our work provides store providers a new approach for modeling business model decisions together with insights of existing business models. This, in turn, supports them in creating new and improving existing business models.
Keywords: Software Ecosystems; Business Models; Variabilities

Debiasing Vandalism Detection Models at Wikidata - Heindorf, Stefan; Scholten, Yan; Engels, Gregor; Potthast, Martin (WWW)

Activate software-based business model development tools: An exploratory study - Szopinski, Daniel (3rd Business Model Conference)

The long tail of taxonomy evaluation criteria: A structured overview - Szopinski, Daniel; Schoormann, T.; Kundisch, Dennis (Proceedings of the 14th International Conference on Design Science Research in Information Systems and Technology (DESRIST))

Can stimuli improve business model idea generation? Developing software-based tools for business model innovation - Szopinski, Daniel (Proceedings of the ACM Creativity & Cognition)
A business model describes the mechanisms whereby a firm creates, delivers, and captures value. Following the steadily growing interest in business model innovation, software tools have shown great potential in supporting business model development and innovation. Yet, understanding the cognitive processes involved in the generation of business model ideas is an aspect of software design-knowledge that has so far been neglected. To investigate whether providing stimuli – in this case, brainstorming questions – can enhance individual creativity in this context, we conduct an exploratory experiment with over 100 participants. Our study is the first to systematically investigate the process of idea generation using a software-based business model development tool with stimuli. Our preliminary findings have the potential to support the future development of business model development tools and to refine the research design used to evaluate such tools.
Keywords: Business model innovation; idea generation; cognitive stimuli; business model development tools; experiment; creativity support system

Squaring the circle: Business model teaching in large classroom settings - Szopinski, Daniel (Journal of Business Models)
Business model innovation is typically taught in small seminars at universities. Teaching this intrinsically task-oriented subject to a large number of students is a challenge. In this paper we address this challenge by proposing an experiential and interactive approach to teaching business models in a large classroom setting.
Keywords: Business model teaching; peer assessment; experiential learning

Bewertung von Maschinen-generierten Geschäftsmodell-Ideen: Eine experimentelle Untersuchung - Seutter, Janina

Vandalism Detection in Crowdsourced Knowledge Bases - Heindorf, Stefan

Teaching business model innovation to large and interdisciplinary IS/IT classes: A didactic approach involving peer feedback via self-recorded video presentations - Szopinski, Daniel; John, Thomas; Kundisch, Dennis (TREO Talks in conjunction with the 40th International Conference on Information Systems (ICIS))